2018
DOI: 10.1111/bcpt.13027
|View full text |Cite
|
Sign up to set email alerts
|

Development of Molecular Therapies for Venous Malformations

Abstract: Vascular anomalies are localized defects of morphogenesis that can affect lymphatic and blood vessels. They are generally called birthmarks, typically observed soon after birth and occurring in up to 10% of children. Based on their clinical and histological characteristics, they are classified into vascular tumours and vascular malformations. The most common malformations are venous malformations (VMs) resulting in chronic vascular diseases that can be associated with significant morbidity necessitating often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…On the other hand, in addition to ligand-specific effects, our in vitro characterization also revealed redundant functions between angiopoietins 1 and 4, suggesting that differential, spatiotemporally regulated expression provides an important mechanism for complementary and sequential roles of angiopoietins to establish retinal circulation system. Moreover, based on reported venous-specific effects of inducible Tie2 deletion in retina ( Chu et al, 2016 ) and over-activating TIE2 mutations in venous malformations ( Kangas et al, 2018 ), Tie2 signaling appears particularly important to venous development that may contribute to the vessel-type-specific phenotype in Angpt4 -/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in addition to ligand-specific effects, our in vitro characterization also revealed redundant functions between angiopoietins 1 and 4, suggesting that differential, spatiotemporally regulated expression provides an important mechanism for complementary and sequential roles of angiopoietins to establish retinal circulation system. Moreover, based on reported venous-specific effects of inducible Tie2 deletion in retina ( Chu et al, 2016 ) and over-activating TIE2 mutations in venous malformations ( Kangas et al, 2018 ), Tie2 signaling appears particularly important to venous development that may contribute to the vessel-type-specific phenotype in Angpt4 -/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Pathologically, VM are composed of disorganized vessels with a thin EC lining, covered by rare, unevenly distributed SMC and poorly organized ECM. 10,11 Previous studies, including ours, have shown that markedly decreased SMC coverage is a prominent hallmark of vascular destabilization in VM, which is associated with dysregulation of perivascular ECM. 10,12 Extracellular matrix regulation involves a dynamic process balanced by ECM deposition and degradation, which is orchestrated by a variety of signal molecules and enzymes.…”
Section: Introductionmentioning
confidence: 82%
“…[24][25][26] Meanwhile, alterations of ECM have been reported in VM previously. 11,27 However, the regulation of perivascular ECM and its potential roles in VM remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…9 Therefore, new treatment modalities for LM are being sought. 10 Until now, the most promising drug has been sirolimus. Sirolimus inhibits TIE2-vascular malformation (VM)-and PIK3CA-VM-induced Akt activation, which is a major molecular abnormality associated with VM.…”
Section: Figurementioning
confidence: 99%